Virtual Training Module for the Extraction of Essential Oils using a Distillation column. - Benalcázar Arroba, Carmen Laura (2023)
The present project considers the development of a training system for a distillation column used for essential oil extraction processes based on the Hardware-in-the-Loop technique. The mathematical model is of the multivariable MIMO type obtained through the heuristic method considering the perturbations. According to the mathematical model obtained from the plant, it is implemented advanced nonlinear control algorithms that consider PID, FUZZY and MPC tech niques. This allows the performance of the proposed controllers to be analyzed by means of the response time. With this information, the stability and robustness of the implemented algorithms are analyzed to evaluate the response of each process and possible errors. The system has an interactive and immersive virtual environ ment through a 3D graphic engine (Unity). The communication is bilateral in real time so that the process can be controlled and monitored. The implemented HMI interface is multifunctional as it can simulate the process in case the real plant is not available. The mathematical model resides in the virtual environment and the control is realized directly from MATLAB; with the real process, it would work as a graphical interface that allows showing the obtained results from the hardware.